A new species of Eocene whitefly—Snotra herczeki sp. nov. (Hemiptera, Sternorrhyncha, Aleyrodidae) from Baltic amber - Drohojowska, Jowita; Bogusiak, Weronika; Kurkina, Sonia; Zmarzły, Marzena; Szwedo, Jacek (Zootaxa, 2023)
The second species of the Aleyrodinae whitefly genus Snotra Szwedo et Drohojowska, 2016 is described based on an inclusion in the Eocene Baltic amber. It is second species of the genus, adding new data to knowledge on disparity and taxonomic diversity of whiteflies in the Eocene Baltic amber. The diversity of the group and its fossil record in the Eocene fossil resins is briefly discussed.